2021
DOI: 10.17691/stm2021.13.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Bacteriophages in the Complex Hydrogel Wound Dressings in vitro

Abstract: Using bacteriophages to overcome the increasing resistance of microorganisms to antibiotics is a novel research venue of clinical importance. Among other challenges, this technique is expected to create and maintain an adequate local concentration of bacteriophages at the site of application. In addition, the possibility of combining the phage preparation with antioxidants and anesthetics may provide new options for stimulating the reparative process.The aim of the study was to assess the viability and lytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Preservation of the bacteriophages’ lytic activity in the hydrogel was confirmed with both in vitro [ 34 ] and in vivo [ 35 ] studies; it was demonstrated that the bacteriophages’ lytic activity in hydrogels based on the Polypran wound dressing was maintained for 4–7 days.…”
Section: Methodsmentioning
confidence: 83%
“…Preservation of the bacteriophages’ lytic activity in the hydrogel was confirmed with both in vitro [ 34 ] and in vivo [ 35 ] studies; it was demonstrated that the bacteriophages’ lytic activity in hydrogels based on the Polypran wound dressing was maintained for 4–7 days.…”
Section: Methodsmentioning
confidence: 83%
“…For topical phage administrations, the formulation needs to be compatible with the application site, be minimally irritating to the skin, be easy to apply and remove, be stable enough to avoid the need for frequent applications, and be bacteriostatic [ 96 , 102 ]. In addition to these challenges, the products for the topical delivery of lytic phages need to maintain the structural integrity and viability of the phage virions, as well as adequate phage concentrations at the site of application [ 103 ].…”
Section: Phage Delivery Strategies For Human Health Applicationsmentioning
confidence: 99%
“…(P. vulgaris, P. mirabilis), Klebsiella spp. (K. pneumoniae, K. oxytoca), Pseudomonas aeruginosa and Escherichia coli Polyvinyl alcohol (PVA), aqueous solution of bacteriophages "Complex Pyobacteriophage" and succinic acid; Polyvinyl alcohol (PVA) and aqueous solution of bacteriophages "Complex Pyobacteriophage" and lidocaine; Polyvinyl alcohol (PVA) and aqueous solution of bacteriophages "Complex Pyobacteriophage" and succinic acid and lidocaine [103] Escherichia coli Polyvinyl alcohol (PVA) hydrogel and bacteriophage [112] Acinetobacter baumannii Sodium alginate, choline oleate and lytic bacteriophages [105] Escherichia coli Sodium alginate, gelatin, and hyaluronic acid for encapsulating acid fibroblast growth factor (aFGF) and bacteriophages [113] Pseudomonas aeruginosa Polycaprolactone (PCL) nanofibers (non-woven textile) and bacteriophages [110] Staphylococcus aureus Beta-glucan (BG), arabinogalactan, gums, and bacteriophages [114] Enterococcus faecalis Alginate-nanohydroxyapatite hydrogel and phages [115]…”
Section: Staphylococcus Aureusmentioning
confidence: 99%